Take a deep breath a book about beingbrave - Graves, Sue; Guicciardini, Desideria (London Franklin watts, 2015)
A series that introduces young children to different emotions and aspects of behaviour, through a fictional story appropriate for the age group
Education
Keywords: Educational psychology